2015
DOI: 10.2465/jmps.141218
|View full text |Cite
|
Sign up to set email alerts
|

Cs–sorption in weathered biotite from Fukushima granitic soil

Abstract: The sorption characteristics of cesium (Cs) ions into weathered biotite with biotite-vermiculite interstratification collected from weathered granodiorite in Fukushima Prefecture, Japan has been investigated. Both single crystals and crushed powder forms of the weathered biotite were experimentally reacted with 20-2000 ppm CsCl aqueous solutions, and analyzed by powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM) to examine the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…One of the most important observations regarding radiocesium adsorption in Fukushima soils is that weathered biotite is a primary adsorbent Mukai et al, 2014Mukai et al, , 2016aMukai et al, , 2016bKikuchi et al, 2015). For example, recent experiments showed that illite and weathered biotite are the primary radiocesium-bearing phases in silt-and sand-size fractions of Fukushima soil (Tanaka et al, 2018).…”
Section: Progress In Experiments Since the Fukushima Accidentmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important observations regarding radiocesium adsorption in Fukushima soils is that weathered biotite is a primary adsorbent Mukai et al, 2014Mukai et al, , 2016aMukai et al, , 2016bKikuchi et al, 2015). For example, recent experiments showed that illite and weathered biotite are the primary radiocesium-bearing phases in silt-and sand-size fractions of Fukushima soil (Tanaka et al, 2018).…”
Section: Progress In Experiments Since the Fukushima Accidentmentioning
confidence: 99%
“…For example, recent experiments showed that illite and weathered biotite are the primary radiocesium-bearing phases in silt-and sand-size fractions of Fukushima soil (Tanaka et al, 2018). Note that biotite in this article is defined as a Fe-rich phlogopite and/or a Mg-rich annite with the chemical formula K(Mg,Fe) 3 AlSi 3 O 10 (F,OH) as identified by X-ray diffraction (XRD), energy dispersive X-ray spectrometry (EDS) and TEM (Kikuchi et al, 2015;Mukai et al, 2016a). Although some observations prior to the Fukushima accident had identified the potential importance of weathered biotite as a Cs adsorbent (Sawhney, 1966;McKinley et al, 2001McKinley et al, , 2004Zachara et al, 2002), this observation is particularly critical in the Fukushima case because weathered granite, which contains weathered biotite, is a dominant source rock in the Fukushima area (Kikuchi et al, 2015;Mukai et al, 2016b;Takahashi et al, 2017).…”
Section: Progress In Experiments Since the Fukushima Accidentmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reviews our recent research with respect to WB in Fukushima, including its structure and Cs-sorption/desorption properties, and discusses the role of WB in the radioactive contamination in Fukushima. Details of the experiments to obtain the results presented here are described in the original papers already published (Mukai et al 2014(Mukai et al , 2016aKikuchi et al 2015;Motai et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its ability to selectively exchange radiocesium, illite and similar clays have been investigated for the possibility of remediating radioactive plumes of cesium. 10 Despite extensive experimental study of ion adsorption at the frayed clay edge and exchange of ions in the clay interlayer [7][8][11][12][13] , the exact mechanism of cesium uptake remains elusive. 14 It is especially unclear how cesium displaces potassium within the interlayer far from the edge in anhydrous interlayers for clays such as illite 11,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%